PENGARUH KUALITAS SARANA PRASARANA DAN TEACHING FACTORY TERHADAP PENINGKATAN PRODUKTIVITAS SISWA KELAS XI TEKNIK KENDARAAN RINGAN DI SMK PERMATA NUSANTARA PATI - Sapuan, Muhamad; Apriyanto, Nuraedhi; Fatra, Fahmy Fatra (Ivet University, 2025)
Several industries have complained about student productivity once they become employees. In response to this low level of student productivity, SMK Permata Nusantara Pati has implemented various efforts, including improving the quality of its facilities and infrastructure and implementing the Teaching Factory learning model. The objectives of this research are: (1) Analyze the influence of the quality of facilities and infrastructure on student productivity; (2) Analyze the influence of the teaching factory learning model on student productivity; (3) Analyze the extent to which the quality of infrastructure and teaching factory learning models together affect student productivity. The type of research used in this research is associative research which is ex post facto in nature. Data collection techniques using questionnaires. The population is 49 students. The tests used are Validity tests and Reliability tests. Test the analysis requirements using the normality test, linearity test, autocorrelation test, multicollinearity test and heteroscedasticity test. Meanwhile, data hypothesis testing uses simple regression tests, multiple regression, T test, F test, R square test (determinant) using the help of the SPSS version 26.0 processing program. -table 0.679 so H1 is accepted. Teaching factory on student productivity has a t-count value of 3.085> t-table 0.679 so that H2 is accepted. There is a positive influence on the Quality of Infrastructure Suggestions and the Teaching Factory Learning Model on the Productivity of Class XI TKRO Students at Permata Nusanatara Pati Vocational School. F test sig value. 0.000 is lower than 0.05 so H3 is accepted. Based on the results of determining the determinant, an r square value of 38.8% was obtained. while the remaining 66.2% is influenced by other variables.